2007
DOI: 10.1097/inf.0b013e318125720a
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Immunologic and Virologic Efficacy After Four Years of Highly Active Antiretroviral Therapy in Human Immunodeficiency Virus Infected Children in Thailand

Abstract: We report the long-term efficacy of highly active antiretroviral therapy (HAART) in 107 antiretroviral-naive human immunodeficiency virus (HIV)-infected Thai children. In an intention-to-treat analysis, 70% of the children had undetectable HIV RNA titers after 192 weeks of HAART. The mean CD4 cell percentage increased from 5.3% to 26.6%. HAART is effective for HIV-infected children in this resource-poor setting despite initiation of treatment in the advanced stage of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
35
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 10 publications
9
35
1
Order By: Relevance
“…There are seven QOL domains including: (1) health perception, (2) physical resilience, (3) physical functioning, (4) psychosocial well-being (for children 5-11 years old only), (5) social and role functioning, (6) health care utilization, and (7) symptoms. The raw scores in all seven domains had different minimum and maximum values, therefore, the raw scores were calculated to simple transformed scores of 0 to 100 with the following formula: transformed score = [(actual raw score -lowest possible raw score)/ (highest possible raw score -lowest possible raw score)] · 100].…”
Section: Quality Of Life Questionnaire and Transformed Scoresmentioning
confidence: 99%
See 1 more Smart Citation
“…There are seven QOL domains including: (1) health perception, (2) physical resilience, (3) physical functioning, (4) psychosocial well-being (for children 5-11 years old only), (5) social and role functioning, (6) health care utilization, and (7) symptoms. The raw scores in all seven domains had different minimum and maximum values, therefore, the raw scores were calculated to simple transformed scores of 0 to 100 with the following formula: transformed score = [(actual raw score -lowest possible raw score)/ (highest possible raw score -lowest possible raw score)] · 100].…”
Section: Quality Of Life Questionnaire and Transformed Scoresmentioning
confidence: 99%
“…[1][2][3] Currently, HIV-infected children treated with highly active antiretroviral therapy (HAART) have increased life expectancy. [4][5][6] Deaths related to HIV/AIDS mortality have decreased significantly, but the non-AIDSrelated conditions maintain a stable trend in children living with HIV-1 after treatment with HAART. 7 Unlike many other chronic illnesses, children with HIV infection are more likely to experience more difficulties in their daily lives (e.g., parental death from AIDS and social stigmatization 8,9 ) which may worsen their QOL.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 In the last decade, highly active antiretroviral treatment (ART) has significantly improved the virologic, immunologic, and clinical outcomes in both adults and children. [4][5][6] Many studies from developed countries using protease inhibitor (PI)-based ART regimen showed an improvement in growth of HIV-infected children after initiating ART. [7][8][9] Studies from Kenya and Uganda also showed significant improvements in weight and height as well as immunological and virologic parameters of perinatally HIVinfected children after ART initiation.…”
mentioning
confidence: 99%
“…Successful virological response has been reported variously, as < 50 [15,23], < 400 [16,21,24] or < 1000 copies/mL [25] in different parts of the world. Based on these cut-offs, response rates of 55% (two months) in China [24] , 74% in Cambodia [16], and 69% (three months) and 70% (two years) in Thailand have been reported [15].…”
Section: Discussionmentioning
confidence: 99%
“…Higher baseline CD4 values and use of NNRTIbased regimens rather than PI-based are two important predictors of faster immunologic recovery [15,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%